A New Surgical Method of Correcting Abnormal Cartilage in Mild or Moderate Cryptotia. Issue 6 (December 2018) - Wang, Yan; He, Zhijuan; Ma, Xu; Li, Qingchun; Li, Ning; Liu, Guofeng
Abstract : Objective: This study aimed to introduce a new technique for the correction of mild or moderate types of cryptotia. Methods: During January 2010 to March 2015, patients with cryptotia deformities came to our hospital and were enrolled in this study. A new surgical method of correction of abnormal cartilage by combining irregular incisions in auricle malformation and directional transplantation of auricular cartilage was designed. The irregular Z shaped flap was designed to correct the skin defects. In the ipsilateral cavum conchae, the auricular cartilage strut was harvested, followed with irregular cartilage incisions and cartilage transplantation. Results: After correction, the corrected auricles in 3 cases showed natural contour with deep auriculotemporal sulcus and no conspicuous scars. The antihelix folding and backward rotation deformities of the auricular cartilage were corrected, and the morphology of superior and inferior crus of the antihelix was not destroyed. One case appeared necrotic. During 1 year of follow-up, there was no incidence of recurrence or revision. Conclusions: The combined techniques for correction of abnormal cartilage are simple and easy to operate, and the reconstructed auricles show natural contour without conspicuous scars. The new technique is suitable for correction of mild and moderate cryptotia.